2015
DOI: 10.1073/pnas.1510814112
|View full text |Cite
|
Sign up to set email alerts
|

Assembly, translocation, and activation of XerCD- dif recombination by FtsK translocase analyzed in real-time by FRET and two-color tethered fluorophore motion

Abstract: The FtsK dsDNA translocase functions in bacterial chromosome unlinking by activating XerCD-dif recombination in the replication terminus region. To analyze FtsK assembly and translocation, and the subsequent activation of XerCD-dif recombination, we extended the tethered fluorophore motion technique, using two spectrally distinct fluorophores to monitor two effective lengths along the same tethered DNA molecule. We observed that FtsK assembled stepwise on DNA into a single hexamer, and began translocation rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…In contrast, FtsK specifically stops on XerCD/dif complexes, which is likely a prerequisite for the activation of recombination (14)(15)(16)25). Because FtsK appears to inhibit the first steps of recombination between dif Ng and dif GGI , we tested its capacity to stop translocating when encountering XerCD Ng / dif GGI complexes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, FtsK specifically stops on XerCD/dif complexes, which is likely a prerequisite for the activation of recombination (14)(15)(16)25). Because FtsK appears to inhibit the first steps of recombination between dif Ng and dif GGI , we tested its capacity to stop translocating when encountering XerCD Ng / dif GGI complexes.…”
Section: Resultsmentioning
confidence: 99%
“…The selection pressure on the XerD-binding site may then reside in the capacity of the dif site to assemble a complex able to stop FtsK, which would require a particular interaction of XerD with its binding site involving bases not directly involved in catalysis. Using single-molecule FRET, it has recently been shown that XerCD/dif complexes may adopt different conformations (25). The nucleotides modified within dif GGI may favor one of these conformations that would not be recognized by FtsK.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon reaching XerCD-bound dif , whether in a synapsed or unsynapsed conformation, it resided briefly and then dissociated without reversal. FtsK C activated recombination when it met synapsed XerCD-dif complexes, and then dissociated before the completion of recombination by XerCD [May et al, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…This DNA motor protein localizes to the bacterial cell division septum and contributes to segregating the sister chromosomes into the daughter cells by translocating towards their replication termini. On chromosome dimers, FtsK stops at the Xer-bound dif sites and activates recombination, triggering resolution of the dimers to monomers (Aussel et al, 2002; Grainge et al, 2011; May et al, 2015). Without FtsK, Xer- dif synaptic complexes are formed, but do not lead to final recombination products (Aussel et al, 2002; Diagne et al, 2014; Grainge et al, 2011; Zawadzki et al, 2013).…”
Section: Introductionmentioning
confidence: 99%